The impact of blinding on the results of a randomized, placebo-controlled multiple sclerosis clinical trial. - Noseworthy, J; Ebers, G; Vandervoort, M; Farquhar, R; Yetisir, E; Roberts, R (1994)
In the randomized, placebo-controlled, physician-blinded Canadian cooperative trial of cyclophosphamide and plasma exchange, neither active treatment regimens (group I: i.v. cyclophosphamide and prednisone; group II: weekly plasma exchange, oral cyclophosphamide, and prednisone) were superior to placebo (group III: sham plasma exchange and placebo medications) using the blinded, evaluating neurologists' assessments of disease course (primary analysis). All patients were examined by both a blinded and an unblinded neurologist at each assessment in this trial. We compared the blinded and unblinded neurologists' judgment of treatment response and analyzed the clinical behavior of patients who correctly guessed their treatment. The unblinded (but not the blinded) neurologists' scores demonstrated an apparent treatment benefit at 6, 12, and 24 months for the group II patients (not group I or placebo; p < 0.05, two-tailed). There were no significant differences in the time to treatment failure or in the proportions of patients improved, stable, or worse between the group II and group III patients who correctly guessed their treatment assignments and those who did not. Physician blinding prevented an erroneous conclusion about treatment efficacy (false positive, type 1 error).